1998
DOI: 10.1016/s0927-7757(97)00079-4
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature rheological behavior of Umbarka waxy crude and influence of flow improver

Abstract: LOW TEMPERATURE RHEOLOGICAL BEHAVIOR OF UMBARKA WAXY CRUDE AND INFLUENCE OF FLOW IMPROVERThe low temperature flow properties; pour point and rheological parameters; have been determined for untreated and additive treated Umbarka waxy crude. The rheological characteristics of the crude showed non-Newtonian yield pseudoplastic flow behavior and pronounced thixotropic effect. Viscometric data are fitted to Bingham, Casson and Herschel-Bulkley plastic flow models using linear and non-linear computer regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Davenport and Somper (1971), for example, showed that the reduction of temperature enlarges significantly the material yield stress. The increase of yield stress, the storage modulus, G′, the loss modulus, G″, and the viscosity with the temperature reduction was also observed by several authors (Wardhaugh and Boger 1987;El-Gamal and Gad 1998;El-Gamal 1998;Remizov et al 2000;Chang et al 2000, Webber 2001Venkatesan et al 2003;Kané et al 2004;Visintin et al 2005;Chen et al 2006;Zhang 2007, 2010;Lopes-da-Silva and Coutinho 2007;Lee et al 2008;Li et al 2009;Oh et al 2009;Hasan et al 2010;Dimitriou et al 2011;Ghannam et al 2012;Rønningsen 2012). The rise of such properties was attributed to wax solubility reduction in oil as the temperature decreases (Venkatesan et al 2003).…”
Section: Introductionsupporting
confidence: 66%
“…Davenport and Somper (1971), for example, showed that the reduction of temperature enlarges significantly the material yield stress. The increase of yield stress, the storage modulus, G′, the loss modulus, G″, and the viscosity with the temperature reduction was also observed by several authors (Wardhaugh and Boger 1987;El-Gamal and Gad 1998;El-Gamal 1998;Remizov et al 2000;Chang et al 2000, Webber 2001Venkatesan et al 2003;Kané et al 2004;Visintin et al 2005;Chen et al 2006;Zhang 2007, 2010;Lopes-da-Silva and Coutinho 2007;Lee et al 2008;Li et al 2009;Oh et al 2009;Hasan et al 2010;Dimitriou et al 2011;Ghannam et al 2012;Rønningsen 2012). The rise of such properties was attributed to wax solubility reduction in oil as the temperature decreases (Venkatesan et al 2003).…”
Section: Introductionsupporting
confidence: 66%
“…20 Then, the crude oil was left at room temperature for 48 hr before any further utilization. 21 The wax precipitation characteristics of Oil M, including the wax precipitation curve, wax content, and WAT were determined by using a differential scanning calorimeter (TA Q20), which has a heat flux controlling accuracy of ±0.1 μW and a temperature controlling accuracy of ±0.05 C. The test specimen (a crucible with waxy crude oil) was first heated to 80 C and held for 1 min to resolve all precipitated wax. Then, the specimen was cooled to −25 C at a cooling rate of 5 C/min.…”
Section: Besides Zhang Et Al Liang Et Al and Wang Et Al Investigatmentioning
confidence: 99%
“…It is also known that the flow behaviors of wax crude oils are also characterized by their shear and thermal history dependence, called the shear and thermal history effect. [5][6][7][8][9] This effect is mainly shown at temperatures below the abnormal temperature. This shear and thermal effect can be attributed to the effect of shear and heating/cooling on the morphology and structure of wax crystals.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the flow behaviors of wax crude oils are also characterized by their shear and thermal history dependence, called the shear and thermal history effect. This effect is mainly shown at temperatures below the abnormal temperature. This shear and thermal effect can be attributed to the effect of shear and heating/cooling on the morphology and structure of wax crystals. ,, Wardhaugh and Boger 5 studied the shear history effect of waxy crude oils and suggested a so-called locus of equilibrium viscosities to replace the rheological model in hydraulic calculations of steadily operating pipelines.…”
Section: Introductionmentioning
confidence: 99%